ENHANCING DIGITAL LITERACY IN ENGLISH TEACHERS THROUGH EDUTECHNO-PRENEURSHIP IN ELT - Maisa; Naufal Ahnaf Widiyana; Muhammad Indraha Sukmana; Muhammad Fikri Fanani; Mahmud (Universitas Duta Bangsa Surakarta, 2026)
Education in the digital era requires English teachers, particularly pre-service teachers, to develop strong digital technology skills. This explorative case study investigates how digital literacy competence supports the development of edutechno-preneurship in English Language Teaching (ELT). The study involved four participants (two pre-service teachers and two in-service teachers) who had experience in conducting online English instruction. Data were obtained through triangulation of semi-structured interviews, digital literacy questionnaires, and classroom and platform observations. The data were analysed using thematic analysis, which generated six main themes: framing edutechno-preneurship, digital literacy competence, technology as a prime mover, personalized learning, flexibility and accessibility, and collaboration and partnership. The findings reveal that three out of four participants (75%) perceived edutechno-preneurship as the integration of education, technology, and entrepreneurship, while one participant emphasized professional self-development. All participants (100%) demonstrated good to very good levels of digital literacy competence. Observational data confirmed their effective use of various platforms, including Zoom, Google Classroom, TikTok, Canva, and YouTube, for both instructional and content-creation purposes. Most participants (75%) positioned technology as a primary driver of their teaching and entrepreneurial practices and implemented personalized and flexible learning approaches in digital environments. Collaboration was reflected through cross-platform engagement and interaction with wider learning communities. These findings indicate that digital literacy competence functions as a foundational enabler in fostering edutechno-preneurship among English teachers in the digital era.